2017
DOI: 10.1111/jfb.13245
|View full text |Cite
|
Sign up to set email alerts
|

Effects of storage time on the motility, mortality and calcium levels of Atlantic salmon Salmo salar spermatozoa

Abstract: This study estimates spermatozoa mortality, morphology, motility and intracellular calcium levels in Atlantic salmon Salmo salar milt after prolonged storage. Milt samples were preserved at 4° C for 25 days and then evaluated for mortality. Motility remained high for the first 3 days and the mortality was low during the first 5 days of storage. A decrease of >50% in calcium content was observed after 5 days of storage. When spermatozoa were activated, calcium levels increased >200% in relative fluorescence uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
(31 reference statements)
2
4
1
Order By: Relevance
“…Nonetheless, higher storage temperatures can be more practical in certain situations such as long distance transportation, since then maintaining low temperatures require specific cooling equipment. Furthermore, studies with salmonids sperm reported lower mortality when sperm was shaken during storage (Parodi et al, 2017), and this way of storing is common in sperm short-term storage protocols of various salmonid species (Trigo et al, 2015;Ubilla et al, 2015). In the present study, no strong effect of stirring was found on sperm preservation.…”
Section: Discussionsupporting
confidence: 37%
“…Nonetheless, higher storage temperatures can be more practical in certain situations such as long distance transportation, since then maintaining low temperatures require specific cooling equipment. Furthermore, studies with salmonids sperm reported lower mortality when sperm was shaken during storage (Parodi et al, 2017), and this way of storing is common in sperm short-term storage protocols of various salmonid species (Trigo et al, 2015;Ubilla et al, 2015). In the present study, no strong effect of stirring was found on sperm preservation.…”
Section: Discussionsupporting
confidence: 37%
“…) and Atlantic salmon (Parodi et al . ), respectively; the Cyprinidae, keeping good‐quality samples (>70%) in common carp and perch ( Perca fluviatilis ) during the first week of storage; Acipenseridae, with more than 50% of motility after 7 days in Siberian sturgeon (Shaliutina et al . ); and marine fish species, where spermatozoa still retained some motility after 30‐day storage in both Atlantic cod and haddock ( Melanogrammus aeglefinus ) (DeGraaf & Berlinsky ).…”
Section: Fish Sperm Motility: a Useful Tool For Multidisciplinary Stumentioning
confidence: 99%
“…Furthermore, studies with salmonids sperm reported lower mortality when sperm was shaken during storage (Parodi et al, 2017), and this way of storing is common in sperm short-term storage protocols of various salmonid species (Trigo et al, 2015;Ubilla et al, 2015). In the present study, no strong effect of stirring was found on sperm preservation.…”
Section: Discussionsupporting
confidence: 37%